PERBANDINGAN EFEKTIFITAS DEXAMETHASON DAN LIDOKAIN DALAM MENCEGAH NYERI TENGGOROKAN SETELAH INTUBASI ENDOTRAKEAL PADA ANESTESI UMUM - John Frans Sitepu (Jurnal Penelitian Keperawatan Medik, 2019)
Throat pain is a complication that is often found in patients with general anesthesia who use endotracheal intubation that is difficult to control even though surgical pain is well controlled using systemic analgesia. The purpose of this study was to see a comparison of the effectiveness of treatment in the prevention of throat pain in general anesthesia. This study used a double blind randomized clinical trial method conducted at three sites. The sample of this study was all patients who underwent elective surgery with general anesthesia endotracheal intubation. Statistically it was shown that there was no difference in effectiveness between Dexamethason 0.2 mg / kg and Lidocaine 1.5 mg / kgBB, but clinically the incidence of sore throat was higher in the Lidocaine group 1.5 mg / kgBB. Whereas at the 6th hour, Dexamethason 0.2 mg / kgBB statistically is more effective than Lidocaine 1.5 mg / kg in terms of reducing the incidence of sore throat after surgery.